2014
DOI: 10.1590/s0103-84782014000200016
|View full text |Cite
|
Sign up to set email alerts
|

Redes neurais artificiais na estimativa da retenção de água do solo

Abstract: Redes neurais artifi ciais na estimativa da retenção de água do solo.Ciência Rural, v.44, n.2, fev, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 9 publications
6
13
0
10
Order By: Relevance
“…Generally, the increased number of neurons per layer does not ensure the best network performance. Similar results were found by Soares et al (2014) and Azevedo et al (2015). An explanation for this is that the increased number of neurons in the network may lead to overfitting, which occurs when the network training process stores the data in the training sample and does not identify the associations between the data in the input and output layers (Silva et al 2010).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Generally, the increased number of neurons per layer does not ensure the best network performance. Similar results were found by Soares et al (2014) and Azevedo et al (2015). An explanation for this is that the increased number of neurons in the network may lead to overfitting, which occurs when the network training process stores the data in the training sample and does not identify the associations between the data in the input and output layers (Silva et al 2010).…”
Section: Resultssupporting
confidence: 91%
“…Ten network architectures were tested to determine a trained network with good fit, with 1, 2, 3, …, 9 and 10 neurons in the hidden layer. Considering that, at the beginning of the training, the free parameters were randomly generated and that these initial values can influence the final result of the training (Soares et al 2014), each ANN architecture was trained 1,000 times. The network with the best fit was selected using the mean squared error (MSE) for the validation sample.…”
Section: Cf Aquino Et Almentioning
confidence: 99%
“…The fact that the ANN with the best results has only one hidden layer agrees with the results observed by Soares et al (2014), who estimated soil water retention using ANN, and Zanetti et al (2008), who estimated reference evapotranspiration using ANNs and concluded that only one hidden layer is sufficient to represent the non-linear relationship between climatic elements and reference evapotranspiration.…”
Section: Resultssupporting
confidence: 83%
“…Soares et al (2015) observed the possibility of using artificial neural networks in the estimation of corn grain yield, considering the morphological variables of the crop. The efficiency of artificial neural networks in the processes of simulation was also observed by Soares et al (2014) in the estimation of bean yield. Castro et al (2013) proposed the use of artificial neural networks in the modeling of growth and stand of eucalyptus located in northern Brazil.…”
Section: Resultsmentioning
confidence: 80%
“…The use of artificial neural networks has presented itself as an efficient alternative to conventional models in the recognition of patterns and simulation of cultivation processes (Silva et al, 2014;Soares et al, 2014). Rogenski et al (2012) found efficiency of the artificial neural networks in the estimation of infection percentage of leaf diseases in wheat, as assistance in decision-making.…”
Section: Resultsmentioning
confidence: 99%